Assessment of functional, sensory, and bioactive properties of crackers enriched with Hom Pathum and black glutinous rice flour - Pattarathitiwat, Paponpat; Panklai, Teerapap; Yousawang, Nattapas; Pongprajak, Apidech; Chuchird, Pornpachen (Journal of Food Technology Research, 2025)
Crackers are widely consumed snack foods known for their thin, dry, and crisp texture. Traditionally, they are produced using soft wheat flour, which is nutritionally limited, as it contains low amounts of vitamins, minerals, and fiber while also having a high glycemic index (GI). To address these shortcomings, this study explored the development of crackers enriched with Hom Pathum (HP) rice and black glutinous (BG) rice flour to enhance their nutritional value. Sensory evaluation results indicated no significant difference among the formulations, suggesting consumer acceptability. The optimal formulation was identified as crackers supplemented with a 40:25 ratio of HP to BG rice flour. Color analysis (L*, a*, b*) revealed statistically significant differences (p < 0.05), showing that higher BG rice flour content produced darker crackers. Microbiological quality met safety standards, with mold and bacterial counts below 1 × 104 and 100 cfu/g, respectively. Nutritional analysis demonstrated considerable bioactive compounds, with total phenolic, flavonoid, and anthocyanin contents recorded at 2.95, 5.70, and 79.05 mg/g (DW), respectively. Functional properties were also promising, as antioxidant activity showed 14.33% and 8.77% inhibition by ABTS and DPPH assays, while α-glucosidase inhibition reached 28.44%. These findings indicate that supplementing crackers with HP and BG rice flour not only improves their nutritional and functional value but also provides consumers with a healthier snack alternative that may contribute to better dietary management and disease prevention.